2017
DOI: 10.1088/1751-8121/aa80f3
|View full text |Cite
|
Sign up to set email alerts
|

${\mathbb Z}_N$ symmetry breaking in projected entangled pair state models

Abstract: We consider Projected Entangled Pair State (PEPS) models with a global ZN symmetry, which are constructed from ZN -symmetric tensors and are thus ZN -invariant wavefunctions, and study the occurence of long-range order and symmetry breaking in these systems. First, we show that longrange order in those models is accompanied by a degeneracy in the so-called transfer operator of the system. We subsequently use this degeneracy to determine the nature of the symmetry broken states, i.e., those stable under arbitra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…In numerical studies, however, it has been always found that if the state jψi has a finite correlation length, then the boundary Hamiltonian is quasilocal (Cirac et al, 2011). With a suitable treatment of sectors, this also holds for symmetrybreaking (Rispler, Duivenvoorden, and Schuch, 2015;Rispler, Duivenvoorden, and Schuch, 2017) and topological (Schuch et al, 2013) phases. More specifically, we can always expand it as…”
Section: Boundary Theorymentioning
confidence: 99%
“…In numerical studies, however, it has been always found that if the state jψi has a finite correlation length, then the boundary Hamiltonian is quasilocal (Cirac et al, 2011). With a suitable treatment of sectors, this also holds for symmetrybreaking (Rispler, Duivenvoorden, and Schuch, 2015;Rispler, Duivenvoorden, and Schuch, 2017) and topological (Schuch et al, 2013) phases. More specifically, we can always expand it as…”
Section: Boundary Theorymentioning
confidence: 99%